2015
DOI: 10.1021/acs.jced.5b00620
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Itaconic Acid from Aqueous Solution onto Ion-Exchange Resins

Abstract: Itaconic acid (IA) is an unsaturated diacid, a promising compound that might replace part of the petrochemical-based monomers, such as acrylic acid, as a building block for polymers. Recent developments in biotechnology allow the efficient production of IA through fermentation processes. However, further enhancements are necessary in the downstream (recovery) of the product. This investigation examined the separation of IA by adsorption from aqueous solutions, using two types of commercial, strongly basic ion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
10
33
0
Order By: Relevance
“…). At pH 2.5 to 3, static sorption capacities up to 0.1 g acid g ‐1 wet resin or sorbent (or up to 0.4 g acid g ‐1 dry product) were determined, in line with other reported work on succinic and itaconic acid . Confirming the work of Li et al ., the weak base products with an acrylic or polystyrene matrix exhibited higher adsorption capacities than the others.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…). At pH 2.5 to 3, static sorption capacities up to 0.1 g acid g ‐1 wet resin or sorbent (or up to 0.4 g acid g ‐1 dry product) were determined, in line with other reported work on succinic and itaconic acid . Confirming the work of Li et al ., the weak base products with an acrylic or polystyrene matrix exhibited higher adsorption capacities than the others.…”
Section: Discussionsupporting
confidence: 85%
“…The wetted material was used in the tests. All results are expressed per g wet weight unless otherwise specified . To determine the water content, a freshly hydrated sample obtained through the procedure described above was dewatered by filtration and then dried at 105 °C for 24 h. It should thus be noted that this is not directly related to the moisture holding capacity which is sometimes provided by the supplier for the shipped material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical industrial process uses a combination of evaporation, centrifugation, and crystallization to recover IA [67]. Magalhaes et al [62] investigated the separation of IA by adsorption from aqueous solution, using two types of commercial strongly basic ion-exchange resins-Purolite A-500P and PFA-300. The results showed that the IA absorption isotherms can be well described with both the Freundlich and Langmuir models and the adsorption kinetics for IA was found to follow a pseudo-second order model.…”
Section: Downstream Processing and Recovery Of Itaconic Acidmentioning
confidence: 99%